Histopathological Evaluation of Excessive Uterine Bleeding of Reproductive Age Group in Hysterectomy Specimens - Naz, Shabana; Afridi, Ehtisham Ahmed khan; Naeem, Shagufta; Naz, Raisa (International Journal of Pathology, 2018)
Objective: Determine the frequencies of uterine pathologies in women of reproductive age group presentingwith excessive uterine bleeding.Material and Methods: This study was conducted in the histopathology section of the Department ofPathology at Ayub Medical College Abbottabad. This was a descriptive study of 100 hysterectomy specimensremoved for excessive uterine bleeding received in the department over a period of six months. All the specimensbelonging to patients of reproductive age group (30-50 years) with excessive uterine bleeding were included inthis study. The data recorded from the specimen request forms included the patients’ clinical presentation,reproductive history and history of hormone intake. All the specimens were received in ten-percent formalin andwere examined grossly. Multiple sections 3-5 microns thick were taken, stained with haematoxylin and eosin andexamined under Olympus Microscope CX23.Result: The most common uterine lesions associated with excessive uterine bleeding were leiomyoma (43%) andadenomyosis (24%).Conclusion: As leiomyoma is the most common lesion found in the uterus of the patients in whichhysterectomy is done for excessive uterine bleeding; this is a treatable cause. As most females are in child bearingage so female of child bearing age should be investigated thoroughly before considering hysterectomy